Expression patterns of Eph genes in the "dual visual development" of the lamprey and their significance in the evolution of vision in vertebrates. Issue 2 (March 2015) - Suzuki, Daichi G.; Murakami, Yasunori; Yamazaki, Yuji; Wada, Hiroshi
SUMMARY: Image‐forming vision is crucial to animals for recognizing objects in their environment. In vertebrates, this type of vision is achieved with paired camera eyes and topographic projection of the optic nerve. Topographic projection is established by an orthogonal gradient of axon guidance molecules, such as Ephs. To explore the evolution of image‐forming vision in vertebrates, lampreys, which belong to the basal lineage of vertebrates, are key animals because they show unique "dual visual development." In the embryonic and pre‐ammocoete larval stage (the "primary" phase), photoreceptive "ocellus‐like" eyes develop, but there is no retinotectal optic nerve projection. In the late ammocoete larval stage (the "secondary" phase), the eyes grow and form into camera eyes, and retinotectal projection is newly formed. After metamorphosis, this retinotectal projection in adult lampreys is topographic, similar to that of gnathostomes. In this study, we explored the involvement of Ephs in lamprey "dual visual development" and establishment of the image‐form vision. We found that gnathostome‐like orthogonal gradient expression was present in the retina during the "secondary" phase; i.e., EphB showed a gradient of expression along the dorsoventral axis, while EphC was expressed along the anteroposterior axis. However, no orthogonal gradient expression was observed during the "primary" phase. These observations suggest that Ephs are likely recruited de novo for the guidance of topographical "second" optic nerve projection. Transformations during lamprey "dual visual development" may represent "recapitulation" from a protochordate‐like ancestor to a gnathostome‐like vertebrate ancestor.